Effect of Mobile Phone Radiation on Reproductive System and Behavior Using Female Albino Mice - Suhera Aburawi; Hana Abusaida; Habiba El Jaafari; Feras Alkayed; Naema Shibani; Arwa Dali; Suliman Shalabi; Marwa Ayad; Omima Altaboni (AlQalam Journal of Medical and Applied Sciences, 2020)
Objectives: To investigate histopathological effect on reproductive system and the behavioral effect in female albino mice due to exposure to mobile phone radiation. Methods: Twelve female albino mice were divided into two groups. Group 1, was healthy mice without expose to mobile phone radiation; group 2, exposed to mobile phone radiation for one hour (ringing) per day for ninety days. At the end of the experiment, behaviour study was carried out using plus maze and forced swimming maze; followed by histological examination of the ovary and uterus. Results: Mice exposed to mobile phone radiation did not show any changes in behavior. While, mice exposed to electromagnetic radiation from mobile phone showed ovarian cortex reduction in number of primordial and primary follicles, absence of oocyte inside the follicle, and large amount of vacuolated cytoplasm in Corpus luteum. In addition, mobile phone radiation exposed mice uterus showed abnormal histological features of the inner mucosa, or endometrium. Glands appears as focal inactive atrophic glands with hyperchromatic nuclei; atrophy of the uterine glands, and number of glands reduction in the stroma were observed. In myometrium, large blood vessels were observed. Conclusion: Exposure to mobile phone radiation has no effect either on behavior or any CNS function during exposure. Histologically, this duration of exposure produced damage in ovary and uterus. It is advised to limit the hours of mobile phone usage each day to keep the mind and body healthy.